PENGEMBANGAN MEDIA EDUGAME BERBASIS WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR IPAS MATERI SUMBER ENERGI SISWA KELAS III DI UPT SD NEGERI TAMBAKBOYO 1 - Saharani Thohiroh; Saeful Mizan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The objective of this study is to ascertain the validity of Wordwall learning media as evaluated by experts, to assess the readability of Wordwall media based on the results of student worksheets, and to determine the appeal of Wordwall media during learning through student responses in grade III at UPT SD Negeri Tambakboyo 1. Students have the opportunity to learn a variety of subjects, ranging from the use of technology to the material presented by teachers through digital learning media. The present study employs a Research & Development (R&D) research design. The research model employed is the ADDIE model, which comprises five stages: analysis, design, development, implementation, and evaluation. The researcher employed a variety of data collection techniques, including interviews, observations, questionnaires, and tests, to gather information for the study. The Wordwall learning media will be designed with an emphasis on aesthetic appeal and alignment with the third-grade IPAS energy sources curriculum, ensuring its capacity to engage students and foster their interest in ongoing learning within a conducive environment.